0920 Behavioral Profiles Associated with the Development of Insomnia Symptoms in Children with Known Mental Health Disorders. (27th May 2020) - Bourchtein, E; Calhoun, S L; Puzino, K; McQuillen, A; He, F; Vgontzas, A N; Liao, D; Bixler, E O; Fernandez-Mendoza, J
Abstract: Introduction: Mental health disorders (MHD) are a known risk factor for the development of insomnia symptoms in youth. However, a number of children with MHD do not go on to develop insomnia symptoms later on in life. Little is known about possible childhood factors that exacerbate or mitigate the risk of developing adolescent insomnia symptoms (AIS) among children with MHD. The present study examined, in an at-risk group of children with MHD, the behavioral profiles associated with the development of AIS. Methods: The Penn State Child Cohort is a random, population-based sample of 700 children (5-12y), of whom 421 were followed up as adolescents (12-23y). Absence of childhood insomnia symptoms was ascertained by parent-reports (n=312), while presence of AIS in this subgroup was ascertained by self-reports (n=97). Presence of MHD was ascertained based on the clinical history and physical exam at baseline (n=52). The Pediatric Behavior Scale (PBS) assessed multiple parent-reported behavioral domains. Results: Children with MHD at baseline had greater levels of difficulty across a variety of internalizing (e.g., anxiety, depression) and externalizing (e.g., impulsivity, hyperactivity) behavioral domains than those without MHD, regardless of whether they developed AIS. However, children with MHD who went on to develop AIS had significantly greater levels of aggressive (p<0.001) and oppositional (p=0.006) behaviors relative to children with MHD who did not develop AIS. In fact, these latter children did not differ from peers without any history of MHD or AIS on levels of aggressive (p=0.820) or oppositional (p=0.436) behaviors. Conclusion: Children with MHD who present with normative aggressive and oppositional behaviors are less likely to develop AIS. Healthcare providers should consider providing preventative sleep interventions to youth with MHD who are exhibiting comorbid externalizing behaviors. Support: National Institutes of Health (R01HL136587, R01HL97165, R01HL63772, UL1TR000127)